Antiretroviral Therapy in Children Less Than 24 Months of Age at Pediatric HIV Centers in Tanzania: 12-Month Clinical Outcomes and Survival. (September 2016) - Naik, Neel Mahesh; Bacha, Jason; Gesase, Anthony E.; Barton, Theresa; Schutze, Gordon E.; Wanless, Richard Sebastian; Minde, Mercy Maria; Mwita, Lumumba Francis; Tolle, Mike A.
Background: Without antiretroviral therapy (ART), approximately one-half of HIV-infected infants will die by two years. In 2010, the World Health Organization (WHO) recommended that all HIV-infected infants < 24 months be initiated on ART regardless of their clinical/immunologic status. However, there remains little published data detailing cohorts of infants on ART in Sub-Saharan Africa. This study describes baseline characteristics and 12 month outcomes of a cohort of HIV-infected children < 24 months of age at pediatric HIV centers in Mwanza and Mbeya, Tanzania. Materials and Methods: Retrospective chart review. Inclusion criteria: children < 24 months of age, initiated on ART at Baylor Children s Foundation Tanzania clinics, between March–December 2011. Results: Baseline : Ninety-three children were initiated on ART at a median age of 13.4 months. Sixty-seven percent had severe immunosuppression and 31.5% had severe malnutrition.Outcome : Seventy-three patients were still in care at 12 month follow-up, there were four (4.3%) deaths, five (5.4%) patients transferred, and 11 (11.8%) loss to follow-up. Average CD4% was 32.7 (p < 0.001). Ninety percent of patients were WHO treatment stage I (p < 0.001). Eighty-six percent had normal nutritional status (p < 0.001). Conclusion: Our cohort of HIV infected children < 24 months initiated on ART did well clinically at 12 month outcomes despite being severely immunocompromised and malnourished at baseline. Nevirapine based regimens had good 12 month clinical outcomes, regardless of maternal exposure. Loss to follow-up rate was high for our cohort, demonstrating the need to develop strong mechanisms to counteract this.